TEORI KENDALA SEBAGAI ALAT PENGUKURAN KINERJA - Budi Kurniawan (Universitas Bunda Mulia, 2017)
Classifying accounting information for internal users of an organizations is one way to support the needs of information for managers. Managerial accounting has three main objectives, namely: (1) provide information for planning activities of the organization; (2) provide information for controlling the activity; (3) provide information to make effective decisions. Theory of constraints is a method used to perform continuous improvement in manufacturing and nonmanufacturing activity. It is characterized as a “thinking process” that begins by recognizing that all resources are limited to the most critical factor that is referred to as a constraint. One of the most interesting issues in the managerial accounting issue is the incentive-based compensation using a balanced scorecard. This research proposes theory of constraints as a performance measurement tool in the four perspectives of the balanced scorecard as an alternative to short-term measurement methods. The outcome framework in this research needs to be proceed to the next stage in upcoming researches.Keywords: constraints, performance measurement, balanced scorecard